Genetic Association of Phosphodiesterases With Human Cognitive Performance - Gurney, Mark E. (Frontiers in Molecular Neuroscience, 2019)
Recent, large-scale, genome-wide association studies provide a first view of the genetic fine structure of cognitive performance in healthy individuals. These studies have pooled data from up to 1.1 million subjects based on simple measures of cognitive performance including educational attainment, self-reported math ability, highest math class taken, and pooled, normalized scores from cognitive tests. These studies now allow the genome-wide interrogation of genes and pathways for their potential impact on human cognitive performance. The phosphodiesterase (PDE) enzymes regulate key cyclic nucleotide signaling pathways. Many are expressed in the brain and have been the targets of CNS drug discovery. Genetic variation in PDE1C, PDE4B and PDE4D associates with multiple measures of human cognitive function. The large size of the human PDE4B and PDE4D genes allows genetic fine structure mapping to transcripts encoding dimeric (long) forms of the enzymes. Upstream and downstream effectors of the cAMP pathway modulated by PDE4D (ADCY1, ADCY8, PRKAR1A, CREB1, or CREBBP) did not show genetic association with cognitive performance, however, genetic association was seen with BDNF, a gene whose expression is modulated by cAMP. Notably absent was genetic association in healthy subjects to targets of CNS drug discovery designed to improve cognition in disease states by the modulation of cholinergic (ACHE, CHAT, CHRNA7), serotonergic (HTR6), histaminergic (HRH3), or glutamatergic pathways (GRM5). These new data provide a rationale for exploring the therapeutic benefit of selective inhibitors of PDE1C, PDE4B and PDE4D in CNS disorders affecting cognition.